An Empirical Study On The Relationship Between Dividend Changes & Future Earning Of The Kuala Lumpur Stock Exchange Listed Companies - Lee, Vooi Ling (2004)
This thesis is concerned with dividend signaling hypothesis which claims that dividends changes have information content and can be used to signal firms’ future prospects. Initially, it was found that dividend change did not support the signaling hypothesis and failed to indicate future earning direction. However when the dividend increased magnitude is taken into consideration, it signals a complex relationship. Small dividend increases will signal future earning increases; whereas large dividend increases will signal future earning decreases.